2020
DOI: 10.47552/ijam.v10i4.1327
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activities of Martynia annua Linn. Root Extract

Abstract: Background: Antioxidants play a significant role to protect harm caused by oxidative stress (OS). Plants having phenolic substances are reported to possess antioxidant properties. The present study was intended to research the antioxidant potential of aqueous extract, Hydroalcoholic extract and Alcoholic extract from Martynia annua root. Martynia annua (cat’s claw, bichu) belongs to Martyniaceae family. For centuries, extracts of leaves, roots, stems, roots and seeds of M. annua have been used to cure eplileps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…We used ethanol as the solvent for our plant extraction based on a previous study conducted by Golestannejad et al [32] that showed the highest inhibition effects from ethanolic extract of olives (Olea europaea) rather than hydroalcoholic extracts on Streptococcus mutans growth, acid production, and adhesion. Another study conducted by Gupta et al [33] also showed that Martynia annua Linn. ethanolic extracts had greater DPPH radical scavenging activity (RSA) than hydroalcoholic and water extracts.…”
Section: Ethanolic Extract Preparationmentioning
confidence: 85%
“…We used ethanol as the solvent for our plant extraction based on a previous study conducted by Golestannejad et al [32] that showed the highest inhibition effects from ethanolic extract of olives (Olea europaea) rather than hydroalcoholic extracts on Streptococcus mutans growth, acid production, and adhesion. Another study conducted by Gupta et al [33] also showed that Martynia annua Linn. ethanolic extracts had greater DPPH radical scavenging activity (RSA) than hydroalcoholic and water extracts.…”
Section: Ethanolic Extract Preparationmentioning
confidence: 85%
“…The nodes are often hard and barely sensitive, and the lymphadenopathy is typically unilateral. (6)(7)(8)(9)(10)(11)(12)(13)(14) Conventionally, aspirin is used for its anti-inflammatory (80 mg/kg/day) and anti-platelet (3 mg/kg/day) properties; nevertheless, it has little effect on the frequency of coronary aneurysms. (15)(16)(17)(18)(19)(20) In some cases, patients who do not respond to IVIG, steroids, and anti-TNF are treated with additional immunosuppressive medications such ciclosporin, cyclophosphamide, methotrexate, and plasma exchange.…”
Section: Discussionmentioning
confidence: 99%
“…UV/Visible spectrophotometer at 517nm was used to determine inhibition percentage. The colour change was observed when it turned from deep violet-light yellow 21,22,23 . Percentage radical scavenging of DPPH was determined by calculation as shown below:…”
Section: Preparation Of Test and Standard Solutionmentioning
confidence: 99%